Evaluasi Kebijakan Transformasi Digital Kesehatan Terhadap Akses, Mutu Layanan, Dan Tata Kelola Keamanan Data - Meutya Zahra Saphira; Nadya Nur Syafina Putri; Riswandy Wasir; Cahya Arbitera (LPPM STIKES Mataram, 2026)
Introduction: Digital health transformation has become a key pillar of Indonesia's health system reform strategy, driven by policies such as the Ministry of Health Regulation (Permenkes) No. 24/2022 on Electronic Medical Records and the development of the SATUSEHAT platform. Objective: This literature review aims to evaluate the impact of digital health transformation policies on three domains: healthcare access, service quality, and health data security governance. Method: A systematic search was conducted in Google Scholar, PubMed, and Garuda databases using keywords including digital health transformation, electronic medical records, telemedicine, data security, and SATUSEHAT, covering publications from 2021 to 2026. Results: Findings indicate that digital health policies have improved service access, particularly through telemedicine expansion in remote areas and the integration of the SATUSEHAT platform. However, unequal digital infrastructure, low digital literacy, and data security vulnerabilities, as evidenced by the 2021 BPJS Kesehatan data breach, remain critical challenges. Conclusion: Indonesia's digital health transformation has improved healthcare access and quality through telemedicine, electronic medical records, and the SATUSEHAT platform. However, unequal infrastructure, workforce readiness, digital literacy, and data security challenges continue to limit its benefits. Strengthening these areas is essential to achieve an inclusive, effective, and secure digital health system.